The impact of the First World War on the Indian commercial class in Natal (Historia, 2021)
The impact of the First World War on the Indian commercial class in Natal At the outbreak of the First World War the Indian the trading class constituted only 10% of the total Indian population. Despite their small numbers, they were a formidable factor in the economy of Natal. Imbued with initiative, trade expertise, and in some cases capital, they established family orientated businesses throughout Natal and monopolised the Indian and the African trade by 1914. As British subjects, they eagerly supported the war effort. It also created economic opportunities for many established businesses who expanded into wholesaling. However, the war also highlighted the unscrupulous nature of some Indian traders who sought to exploit existing conditions for personal gain. This profiteering by several merchants and retail dealers created further divisions and hostility between the trading and non-trading sections of the Indian population. The latter were also targets of petty White traders whose resentment unleashed a wave of anti-Indianism during and after the First world war. This article will examine the impact of the war on Indian family businesses and the nature of trade relations which existed among the various racial groups in Natal.
Keywords: First World War; economy of Natal; African trade; British subjects; Indian traders; White traders; anti-Indianism; Indian family businesses